Replication of adenovirus DNA-protein complex with purified proteins. - Ikeda, J E (1981)
A protein fraction isolated from the cytosol of adenovirus-infected HeLa cells, which contained DNA polymerase alpha, catalyzed adenoviral DNA replication in the presence of adenovirus DNA binding protein, eukaryotic DNA polymerase beta, ATP, all four dNTPs, and MgCl2. DNA replication started at either end of exogenously added adenoviral DNA and was totally dependent on the presence of terminal 55,000-dalton proteins on the DNA template. The replicaton of adenovirus DNA in the system was sensitive to aphidicolin and retained nearly all the properties of DNA replication that occur in vivo or in vitro with crude extracts. The 5'-ends of the newly synthesized adenovirus DNA strands were covalently linked to an 80,000-dalton protein linked to dCMP. DNA synthesized with purified proteins was only 25-50+ the length of parental viral strands. Addition of cytosol extracts from uninfected HeLa cells to reaction mixtures containing purified proteins gave full-length adenoviral DNA strands.